IMPLICATIONS OF MERDEKA BELAJAR KAMPUS MERDEKA (MBKM) AT JENDERAL ACHMAD YANI UNIVERSITY - Aam Rachmat Mulyana; Ade Sobandi; Janah Sojanah (JURNAL ILMIAH EDUNOMIKA, 2023)
This research has the aim of how the readiness of both students and the campus of the Study Program (Prodi) and the Faculty of Economics and Business (FEB) of Jenderal Achmad Yani University in welcoming, implementing and evaluating linearly. The advantages offered are not only aimed at increasing student skills but there are still shortcomings in their implementation, starting with the fact that there are still many students who lack information about MBKM. A total of 279 students filled out an online questionnaire and answered according to what they knew. The majority of students are interested in this MBKM program as evidenced by 66% choosing it. This is not in line with the readiness of students and the campus. Through this research, it is hoped that the evaluation of both parties can be the basis for future corrections.